Ecological nostalgias memory, affect and creativity in times of ecological upheavals - Angé, Olivia 1981-; Berliner, David 1976- (Berghahn Books, 2021)
"Introducing the study of econostalgias through a variety of rich ethnographic cases, this volume argues that a strictly human centered approach does not account for contemporary longings triggered by ecosystem upheavals. In this time of climate change, this book explores how nostalgia for fading ecologies unfolds into the interstitial spaces between the biological, the political and the social, regret and hope, the past, the present and the future"--
Keywords: Soziale Situation; Ethnoökologie; Umweltveränderung; Humanökologie; Human ecology / Case studies; Ethnoecology / Case studies; Global environmental change / Social aspects / Case studies; Nostalgia / Social aspects / Case studies; Ethnoecology; Global environmental change / Social aspects; Human ecology; Case studies; Aufsatzsammlung